P429 Factors associated with weight gain in patients treated with anti-TNF-α for inflammatory bowel disease: a cohort study. (25th January 2019) - Haas, M; Abitbol, V; Paupard, T; Chaussade, S; Nahon, S
Abstract: Background: Previous studies have shown weight gain in patients with spondyloarthritis treated with anti-TNF. This weight gain could be explained by both the orexigenic effect of anti-TNF. However, other factors could be involved such as diet changes, limited physical activity, and socioeconomic deprivation. The aim of the study was to identify factors associated with weight gain in patients treated with anti-TNF for IBD. Methods: Consecutive IBD patients treated with anti-TNF were included in a multi-centre study (Groupe Hospitalier Intercommunal de Montfermeil, Hôpital Cochin Paris, Centre Hospitalier de Dunkerque). Most of the patients were attending the outpatient clinic for anti-TNF infusion. They were asked to answer questionnaires about (1) disease activity; (2) quality of life (sIBDQ); (3) fatigue (FACIT); (4) physical activity; (5) socio-economic level (EPICES score); 6) anxiety and depression (HAD score). All the patients had an interview with a dietician. IBD's characteristics were extracted from the prospective data base Focus_MICI®, shared by the three centres. Patients were divided in two groups: (1) patients with more than 10% weight gain since anti-TNF initiation; (2) patients with less than 10% weight gain. The two groups were compared using univariate analysis. Results: One hundred and thirteen patients [sex ratio (F/M) 51/62, mean age 41 years] were included from January to July 2018. Sixty-nine (61%) had Crohn's disease and 44 (38%) had ulcerative colitis. Mean disease duration was 10.3 years and mean anti-TNF duration was 3.8 years. Anti-TNF were given for luminal CD in 56% and refractory UC in 69%. Twenty-one (30%) patients had previous digestive surgery. Seventy-one (62%) patients had clinical remission. Thirty-nine (34%) patients had more than 10% weight gain since anti-TNF initiation. Patients with weight gain >10% were significantly more deprived ( p < 0.02), more sedentary ( p < 0.05) and had more high carbohydrate diets ( p < 0.05). However, remission rate was higher in patients with less than 10% weight gain ( p < 0.04). Age, sex ratio, tobacco use, first-degree relative history of obesity, corticosteroids for more than 4 weeks, mean CRP, levels of anxiety or depression, and fatigue were not statistically different between the two groups. Optimisation of treatment was not statistically different between the two groups. Conclusions: In this study, one third of the patients had a weight gain of more than 10% since anti-TNF therapy initiation. Weight gain was associated with socioeconomic deprivation, limited physical activity, high-carbohydrate diet, and lower remission rates. These results should be confirmed but already suggest the need to include IBD patients into physical activity and nutrition education Programmes.